Clinical Efficacy of a Position-Responding Mandibular Advancement Device in Patients With Obstructive Sleep Apnea - Sung-Woon On; Dong-Kyu Kim; Min Hyuk Lee; Ji Hae Lee; Kyung Chul Lee; Soo-Hwan Byun; Seok Jin Hong (Clinical and Experimental Otorhinolaryngology)
Objectives. Although mandibular advancement device (MAD) treatment is effective for obstructive sleep apnea (OSA), some concerns remain regarding its potential therapeutic impact and side effects. Thus, we developed a novel MAD that auto-titrates depending on its position in patients with OSA. We conducted a clinical trial to determine the efficacy of an auto-titrating mandibular advancement device (AMAD) for treating OSA. Methods. Fourteen patients diagnosed with OSA participated in this study. Polysomnography (PSG) was performed at the beginning of the clinical trial, and after 3 months of treatment, PSG with AMAD in situ was conducted. Results. The mean scores for the Epworth Sleepiness Scale (ESS) and STOP-Bang were 8.21±4.21 and 5.00±1.00, respectively. After 3 months of AMAD treatment, the STOP-Bang scores improved to 3.75±1.06; however, the ESS scores did not show a significant change. Additionally, we observed statistically significant improvements in several respiratory parameters in the PSG data following AMAD treatment. These included reductions in the apnea-hypopnea index (AHI) (from 32.85±21.71 to 12.93±10.70), supine AHI (from 45.91±23.58 to 15.59±12.76), and lateral AHI (from 13.94±10.95 to 5.49±7.40). Improvements were also noted in the lowest O2 saturation (from 79.71±6.22 to 84.00± 5.71), total arousal number (from 191.14±112.07 to 86.57±48.80), and arousal index (from 33.76±21.00 to 15.05± 8.42). However, there were no significant changes in total sleep time, sleep efficiency, or mean oxygen saturation. Additionally, no major side effects were observed during treatment, specifically related to tooth or jaw pain. Conclusion. Our clinical trial found that AMAD improved PSG parameters and reduced the incidence of common side effects. Therefore, AMAD may be an effective alternative treatment for OSA.